IMPLEMENTASI MODEL EVALUASI CIPP PADA PELAKSANAAN PEMBELAJARAN MATEMATIKA DALAM PROGRAM MERDEKA BELAJAR DI SEKOLAH DASAR - FADLI, SAIFUL; SUPRATMAN, MOH.; MAHYUNI, SAADATUL (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
Study This use approach qualitative descriptive and analyzed with the CIPP model. The CIPP model is formed from four dimensions evaluation that is evaluation Context, Input, Process, and Product. Objective study This is for know How implementation learning mathematics in the independence program studied at SDN Bunpedek. subject study This are teachers and students class IV and class V consisting from 2 teachers, students class IV amounted to 25 people meanwhile student class V amounted to 23 people. Instrument data obtained through observation and analysis document. Research results can concluded as following: 1) Reference base used in carry out learning mathematics in the independent program Study based the basics law implementation curriculum loaded independence in Permendikbudristek. 2) In context Power support schools, teacher qualifications, and facilities are very adequate. Teacher readiness input context, readiness students, curriculum, and learning media are very supportive. From the context of the activity process learning mathematics Already held in accordance process standardization. Context output/product results mark Student Final Examination (UAS) and grades results project student in study very well. ABSTRAKPenelitian ini menggunakan pendekatan kualitatif deskriptif dan dianalisis dengan model CIPP. Model CIPP terbentuk dari empat dimensi evaluasi yaitu evaluasi Contex, Input, Process, dan Product. Tujuan penelitian ini adalah untuk mengetahui bagaimana pelaksanaan pembelajaran matematika dalam program merdeka belajar di SDN Bunpedek. Subjek penelitian ini adalah guru dan siswa kelas IV dan kelas V yang terdiri dari 2 orang guru, siswa kelas IV berjumlah 25 orang sedangkan siswa kelas V berjumlah 23 orang. Instrumen data diperoleh melalui observasi dan analisis dokumen. Hasil penelitian dapat disimpulkan sebagai berikut: 1) Acuan dasar yang digunakan dalam melaksanakan pembelajaran matematika pada program merdeka belajar berlandaskan dasar-dasar hukum implementasi kurikulum merdeka yang termuat dalam Permendikbudristek. 2) Secara konteks daya dukung sekolah, kualifikasi guru, dan sarana sangat memadai. Konteks input kesiapan guru, kesiapan siswa, kurikulum, dan media pembelajaran sangat mendukung. Dari konteks proses kegiatan pembelajaran matematika sudah dilaksanakan sesuai standarisasi proses. Konteks luaran/produk hasil nilai Ujian Akhir Siswa (UAS) dan nilai hasil proyek siswa dalam belajar sangat baik.